2002
DOI: 10.1006/dbio.2002.0684
|View full text |Cite
|
Sign up to set email alerts
|

The Cdk5 Homologue, Crp, Regulates Endocytosis and Secretion in Dictyostelium and Is Necessary for Optimum Growth and Differentiation

Abstract: Dictyostelium Crp is a member of the cyclin-dependent kinase (Cdk) family of proteins. It is most related in sequence to mammalian Cdk5, which unlike other members of the family, has functions that are unrelated to the cell cycle. In order to better understand the function of Crp in Dictyostelium, we overexpressed a dominant negative form, Crp-D144N, under the control of the actin 15 promoter. Cells overexpressing Crp-D144N exhibit a reduced growth rate in suspension culture and reduced rates of fluid-phase en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…PsaA is a binding partner of Cdk5 (17). D. discoideum cells expressing a dominant negative form of Cdk5 grow 3 times slower and produce 80% less spores than the wild type (46). Treatment of cells with roscovitine, an inhibitor of Cdks, also inhibits D. discoideum growth and spore cell differentiation (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PsaA is a binding partner of Cdk5 (17). D. discoideum cells expressing a dominant negative form of Cdk5 grow 3 times slower and produce 80% less spores than the wild type (46). Treatment of cells with roscovitine, an inhibitor of Cdks, also inhibits D. discoideum growth and spore cell differentiation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NumA1 likely regulates the cell cycle and plays a role in pstO cell differentiation. Cdk5 is a nucleoplasmic and cytoplasmic protein that regulates growth and spore cell differentiation in D. discoideum (17,18,46).…”
mentioning
confidence: 99%
“…1C,D). Cdk5 activity had previously been shown to be required for optimal cell proliferation in Dictyostelium [Sharma et al, 2002]. Therefore, a strain over-expressing a Cdk5-GFP fusion protein [AX3/ [act15]:cdk5:GFP; Huber and O'Day, 2011a] was used to analyze the effect of Cdk5-GFP over-expression on roscovitine-inhibited axenic growth.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have linked Cdk5 dysregulation to advanced melanoma and neurodegenerative diseases such as amyotrophic lateral sclerosis and Alzheimer's disease [Dhavan and Tsai, 2001; Lee et al, 2010;Abdullah et al, 2011;Crews et al, 2011]. In Dictyostelium, Cdk5 has been shown to be required for optimal growth and differentiation, however, attempts to generate a knockout mutant have been unsuccessful [Sharma et al, 2002]. A recent study showed that Cdk5 localizes to both the nucleus and cytoplasm in Dictyostelium and binds to puromycin-sensitive aminopeptidase A [PsaA; Huber and O'Day, 2011a].…”
mentioning
confidence: 98%
“…86 PFTAIREs emerged in metazoans and are present in species that lack a nervous system, e.g., in demosponges. In contrast, true PCTAIRE kinases ("CDK16"-homologs) are only present in animals, again supporting the hypothesis that these kinases might have an important role in neurons.…”
Section: Pctaires and Pftaires: Eumetazoan-specific Genesmentioning
confidence: 99%